Emission of volatile organic compounds (VOCs) from application of commercial pesticides in China. (15th July 2022) - He, De-Chun; Li, Fang-Hong; Wu, Mian; Luo, Hui-Li; Qiu, Li-Qing; Ma, Xiao-Rui; Lu, Jia-Wei; Liu, Wang-Rong; Ying, Guang-Guo
Abstract: Applying pesticides can result in emissions of volatile organic compounds (VOCs), but little is known about VOC emission characteristics and the quantities in particular regions. We investigated the use of pesticides in China based on a large-scale survey of 330 counties in 31 provinces and evaluated the national pesticide VOC emission potentials based on thermogravimetric analysis of 1930 commercial pesticides. The results showed that herbicides were the most extensively used pesticide category in China, accounting for 43.47%; emulsifiable concentrate (EC), suspension concentrate, and wettable powder were the dominant pesticide formulations, with proportions of 26.75%, 17.68%, and 17.31%, respectively. The VOC emission potential coefficient (EP) of the liquid formulations was higher than the solid formulations, and the maximum mean EP was 45.59% for EC and the minimum was 0.76% for WP. Among 437 high-VOC pesticide products used in China, EC accounted for 83.52%, and 16.93% of those contained abamectin. The total VOC emissions derived from commercial pesticides in China were 280 kt (kilotons) in 2018, and 65.35% of the contribution was derived from EC. Shandong, Hunan, and Henan were the three provinces with the highest pesticide VOC emissions (>21 kt/y). The emission rate of VOCs from pesticides was 24.80 t/d in China, which was higher than in San Joaquin Valley, California. These findings suggest that some comprehensive measures (e.g., perfecting pesticide management policy, strict supervision for pesticide production and use, and strengthening pesticide reduction publicity) should be taken to reduce VOC emissions from pesticide applications. Graphical abstract: Image 1 Highlights: Emulsifiable concentrate (EC) is the most widely used formulation in China. Liquid formulations have higher VOC emission potentials than solid formulations. Abamectin is the most prevalent active ingredient in high-VOC pesticide products. EC contributed the highest (65.35%) pesticide VOC emission quantity in China. Pesticide VOC emission rate of China is obviously higher than in San Joaquin Valley.